IoT Based Smart Parking Monitoring Using Labview and Node MCU - P. Vishnu Kumar; Kammari Dinesh; Talari Bharath Kumar, P. Jelan Basha, G. Hari Prasad (Journal of Electronic Design Engineering, 2021)
This paper is regarding planning a PC-based observance parking system supported IoT that may be applied at the park-like at the searching advanced and offices. This paper focuses on the event of front panel victimization National Instrument’s LABVIEW package and Node MCU, Personal Computer (PC), and NODE MCU. The traditional parking lot system doesn’t have a board and it cannot show the vacancy of automobile parking space. The user must gamble to hunt any vacancy and need to watch for the opposite automobile to exit from the automobile parking space. Up to the traditional parking system, it’ll create the automobile parking space become well organized and user friendly. This paper can produce an automobile detection system by developing a PC-based front panel of parking lot operation knowledge. The system can convert the output from the sensing element to the programmable language to the computer-based mostly board. The board aims to indicate the standing and automobile parking space vacancy. The NODE MCU is employed to supply interfacing between hardware and package. By victimization Lab, VIEW, and Node MCU, the simulation of the physical system will be developed to watch the quantities to be measured and the standing of the instrumentation within the plant from remote purposes while not accessing the inaccessible areas of the plant. Through the traditional parking system victimization Lab VIEW and Node MCU, the front panel is with success developed and explained by planning a physical model of automobile parking space with automobile detector operation. These PC-based observance systems will be applied in varied industrial applications like building security systems and mill automation.